THE EFFECT OF BALL GAME ON THE STUDENTS' ENGLISH VOCABULARY MASTERY AT SECOND GRADE OF SMPN 7 KERINCI - Yenti, Linda Susri (Langue (Journal of Language and Education), 2023)
This research aimed to see the effect of Ball Game on students' English vocabulary mastery. Therefore, the researcher used a quantitative method with an experimental research design to obtain the research objectives. There were 2 classes that participated in this research. It consisted of VIII D as control class VIII B as the experiment class. each class consisted of 26 students, so the sample total are 52 students. to collect the data, 25 multiple questions were used to test the students. the finding showed Ball game significantly affects students’ English vocabulary at SMPN 7 Kerinci. It was proved by the vocabulary test value of the post-test between the classes. The post-test result showed the differences in the result achieved by the tough control class without using Ball game with the experimental class which was tough by using Ball game. The means score becomes one of proof of this statement. Based on the mean score, it was found that the control class have 60.77 and the standard deviation was 10.24. Meanwhile, the experimental class was 64.61 and the standard deviation was 12.96. besides The result of t-test showed that tobs= 1,26 > ttable= 1,93. The researcher proposed several recommendations to gain better improvements.